Identifikasi Senyawa Aktif Ekstrak Buah Mengkudu (Morinda citrifolia L.) dan Potensinya sebagai Antioksidan - Sogandi Sogandi; Rabima Rabima (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Antioxidants are compounds that can inhibit oxidation reactions by binding to free radicals and highly reactive molecules. One form of reactive oxygen compounds is free radicals, these compounds are formed in the body and are triggered by various factors. Noni fruits have been used by the community as a medicine for high blood pressure, beriberi, urinating, inflammation of bile, inflammation of the intestine, dysentery, constipation, spleen pain, liver pain, diabetes and lumbago. Nevertheless, research on the identification of the active compounds of noni fruit which act as antioxidants yet. This study aims to extract and fractionation of Noni fruit, determine the antioxidant activity of Noni fruit extract, and identify the types of bioactive compounds that act as antioxidants. Noni fruit was extracted used maceration technique with 96% ethanol and then fractionated using n-hexane, chloroform and ethyl acetate solvents. Antioxidant activity from the results of noni fruit fractionation was measured by the DPPH (1.1 diphenyl-2-picrylhydrachyl) method and identification of bioactive compounds was carried out by GCMS. The results showed the greatest antioxidant activity was found in chloroform fraction with a percentage of inhibition of 78.19%. For the first time this study revealed the types of bioactive compounds from noni fruit ethyl acetate fraction which act as antioxidants are n-hexadecanoic acid, squalene, pyridin-3-carboxamide, oxime, n- (2-trifluoro methyl phenyl), and beta-sitosterol